Alopecia in Patients with Autoimmune Hepatitis Treated by Tacrolimus Therapy - Yüksekyayla, Osman; Batıbay, Ersin; Wahlin, Staffan; Efe, Cumali (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Yüksekyayla O, Batıbay E, Wahlin S, Efe C. Alopecia in patients with autoimmune hepatitis treated by tacrolimus therapy. Turk J Gastroenterol. 2025;36(1):67-68.